Phytochemical analysis and anti-aging efficacy of two Egyptian sweet potato cultivars in a d-galactose-induced skin aging model - Rehab M. Elgabry; Ghada A. Fawzy; Khaled M. Meselhy; Nehal M. Ramadan; Nihal Farid Younes; Areej M. Al-Taweel; Shagufta Perveen; Mohamed S. Sedeek (Future Journal of Pharmaceutical Sciences)
Abstract Background Sweet potato (Ipomoea batatas (L.) Lam.) is a member of the family Convolvulaceae. Much research has highlighted its variable biological actions in the treatment of many disorders. Our study focused on the quantitative analysis of two Egyptian sweet potato cultivars (Abees and A195). First, we applied proximate analysis, measured total phenolic, and flavonoid contents, performing an HPLC standardization of their ethanolic extracts using chlorogenic acid standard. Furthermore, the two cultivars were formulated as topical creams (3% w/w and 5% w/w) and evaluated for their anti-skin aging activity in a d-galactose-induced skin aging mouse model. Results revealed that both cultivars have high nutritional importance. Results Abees exhibited higher total phenolic and flavonoid contents than A195, while A195 contained a higher concentration of chlorogenic acid. Both cultivars showed a concentration-dependent anti-skin aging activity, with 5% Abees cream demonstrating the lowest visual skin-aging score, the highest activity of catalase (CAT) and superoxide dismutase (SOD), and the lowest concentration of malondialdehyde (MDA). Restoration of skin thickness and collagen content was observed in the 5% Abees group, while both Abees and A195 caused a noticeable concentration-dependent decrease in the skin SMAD7 expression. Decreased SMAD7 has been correlated to upregulating the TGF-β/SMAD3-induced collagen production in aged skin. Conclusion This study elaborates the nutritional importance, phenolic and flavonoid content and anti-skin aging activity of Abees and A195 roots and we recommend further preclinical and clinical investigations of sweet potato.